Northrop Frye's notebooks and lectures on the Bible and other religious texts - Frye, Northrop (Frye, Northrop. Works. 1996, 2003)
In the third published volume of Canadian literary critic Frye's (1912-91) 77 holograph notebooks, the material is mostly from the 1970s, when he was writing the first of his books on the Bible, The Great Code. However, it begins with Notebook Three from the late 1940s in which he writes primarily on religious themes. It concludes with Notebook 23 from the middle 1980s, written between his first and second book on the Bible; and one from the 1960s devoted largely to his reading of Dante's Purgatorio and the first ten cantos of the Paradiso. Altogether the volume contains 11 notebooks, three sets of typed notes, and a transcription of 24 lectures on The Mythological Framework of Western Culture in 1981-82. Annotation (c)2003 Book News, Inc., Portland, OR (booknews.com).